Prototipe Pengukuran Kadar Gula dalam Tubuh Manusia Melalui Urin - Mohammad Hafiz Hersyah; Budi Rahmadya; Gentha Wijaya (Jurnal Rekayasa Elektrika, 2019)
In this research, we propose a prototype to measure glucose index in human body after applying benedict reagen into urine samples. This system divides into two main components that are identification device and android smartphone. The identification device consists of TCS3200 colour sensor and a raspberry pi. The TCS3200 colour sensor's function is to predict the alteration of urine sample and determine the colour category according to the benedict rule and to measure the glucose in the sample. The Raspberry pi function is to process the data that acquired from the colour sensor. By optimizing with Tsukamoto Fuzzy Logic Control, the research successfully identifies the glucose by achieving 100% and the result of fuzzy logic control on Raspberry Pi as decision making by urine in 90% and by conflicting minimum error in 5.6%.